Implementing Monetary Policy after the 2008 Financial Crisis - Kallianiotis, Ioannis N. (Archives of Business Research, 2019)
Every six weeks or so (9 times during the year), the financial world watches as the Federal Open Market Committee (FOMC) decides on a target interest rate in the federal funds market for the next period. But what happens next? How do policymakers make sure that interest rates in the fed funds market trade within the target range? What will be the effect of the new target rate on the Wall Street and the Main Street? How efficient is so far the monetary policy after the latest global financial crisis? Is the target rate the correct one? The framework that the FOMC uses to implement monetary policy has changed over the last decade and continues to evolve today. Before the 2008 financial crisis, policymakers used one set of instruments to achieve the target rate. However, several policy interventions introduced soon after the crisis drastically altered the landscape of the federal funds market. This new and uncertain environment, with enormous reserves, necessitated a new set of instruments for monetary policy implementation. Lately, after December 2015, as the FOMC began to unwind the effects of these policy interventions, some questions arise: What rules will be followed by the Fed? What happens next as the federal funds market converges to a “new normal”? How effective will be the new policy? Can the Fed prevent a new crisis? The federal funds rate is very low and affects negatively the financial markets (bubbles are growing), the real rates of interest, and the deposit rates, which means the true economic welfare is falling and a new global recession is in preparation, if the latest easy money policy will continue.